Effects of Particulate Matters on Cardiovascular Disease - Jun-ichi OYAMA; Koichi NODE (The Journal of Balneology, Climatology and Physical Medicine, 2017)
[Abstract] Recently, air pollution by particlate matter (PM) including PM2.5 (less than 2.5 micron in diameter) and ultrafine particle (UFP: less than 0.1 micron in diameter) is raising important issue for cardiovascular and respiratory disease in Japan. In western Japan, Asian dust (yellow sand) flying in the early spring is affecting human daily life. Moreover, volcanic ashes also influence human activity that is living around the volcanic area. Increased PMs is known to be usually caused by industrial activities and/or natural disasters. Acute exposure has been linked to a range of adverse cardiovascular events, including hospital admissions with angina, myocardial infarction, and heart failure. Long-term exposure is thought to promote the atherosclerosis and impair cardiovascular risk factors. Recent experimental and epidemiologic studies show that PM2.5 is able to reach the small airways and terminal alveoli, and UFP can also be translocated directly into the systemic circulation, which lead to the releases of immunological, oxidative and inflammatory mediators, autonomic nervous system imbalance, and endothelia dysfunction resulting in impairment of cardiovascular risk factor and diseases. In this review, we would like to discuss the influence of PM2.5 on cardiovascular disease.